(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In its broadest sense, education is a cultural process. This process transforms each new born infant from biological to social being. According to Spencer education must conform to the natural process of mental evolution-that there is a certain sequence in which the faculties spontaneously develop, and certain kind of knowledge which each requires during its development and supply this knowledge. While speaking on education he discusses three different types of education i.e. intellectual, moral and physical education. For him in intellectual education the process of self development should be encouraged to the uttermost. Children should be led to make their own investigation, and draw their own inferences.